Os efeitos na arrecadação do ICMS de contribuintes do Ceará antes e depois da implantação de anistias tributárias - Eccard, Maykon Taveira (2016)
Tax amnesties are an important government instrument. Be simply to recovery delinquent taxpayers or to increase revenue and meet cash shortages, amnesties have become a common practice, which is repeated periodically. In the last twenty years, the State of Ceará edited several state laws, establishing tax amnesty programs. However, there isn't in the national literature records of the economic result of these programs. The objective of this study is to evaluate the effects of the programs about the behavior of benefited firms following the granting of amnesty regarding the collection of ICMS, specifically evaluate the tax amnesty in 2009, adopted by the state of Ceará. Using the difference in differences model and the quantile regression method, evidences were obtained that indicates the negative effect of the tax amnesty over the ICMS collection of the companies that used the benefit, only the first quantiles of the distribution.